2020
DOI: 10.1002/acn3.51196
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Alzheimer's neurodegenerative biomarkers and their clinical outcomes

Abstract: Objective: In the 2018 ATN framework, Alzheimer's neurodegenerative biomarkers comprised cerebrospinal fluid (CSF) total tau, 18 F-fluorodeoxyglucose-positron emission tomography, and brain atrophy. We aimed to assess the clinical outcomes of having discordant Alzheimer's neurodegenerative biomarkers. Methods: A total of 721 non-demented individuals from the Alzheimer's Disease Neuroimaging Initiative database were included and then further categorized into concordant-negative, discordant, and concordant-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 44 publications
(107 reference statements)
0
9
1
Order By: Relevance
“…There is, however, some support that HV is associated with cognitive decline and progression more strongly than t-tau. 13 - 15 Although in our study we found t-tau as individual biomarker also predicted clinical progression and cognitive decline, the high correlation with p-tau hampers the addition of t-tau to a model with Aβ and p-tau, making it a less desirable biomarker to use in the AT(N) classification. NfL and GFAP have both been shown to be related to baseline cognition, cognitive decline, and clinical progression as individual predictors, but have not yet been studied extensively in comparison to other N biomarkers.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…There is, however, some support that HV is associated with cognitive decline and progression more strongly than t-tau. 13 - 15 Although in our study we found t-tau as individual biomarker also predicted clinical progression and cognitive decline, the high correlation with p-tau hampers the addition of t-tau to a model with Aβ and p-tau, making it a less desirable biomarker to use in the AT(N) classification. NfL and GFAP have both been shown to be related to baseline cognition, cognitive decline, and clinical progression as individual predictors, but have not yet been studied extensively in comparison to other N biomarkers.…”
Section: Discussioncontrasting
confidence: 54%
“…The low correlation between N biomarkers likely contributes to the often discordant biomarker results in the AT(N) classification. 6 , 9 , 12 , 15 We add blood-based biomarkers to the comparison, showing similarly modest associations with the N biomarkers in other modalities, and also similarly strong associations with clinically relevant outcomes. Although at a population level, the overall qualitative pattern of biomarker frequencies remains rather stable regardless of the type of biomarkers used, 9 it becomes problematic when researchers and clinicians treat the different N biomarkers as if they were identical.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations